Purpose-driven leadership for sustainable business: From the Perspective of Taoism - Liangrong Zu (International Journal of Corporate Social Responsibility (JCSR), 2019)
In recent years, the topic of "purpose" has been actively studied and discussed by the academic scholars and business practitioners. The purpose revolution has significantly changed the way companies are doing business today. There is a growing consensus among leaders today that business exists not to make money, but to make the world a better place to live in. Companies have been increasingly demanded by stakeholders to do more than to provide good products, good services, good prospects, and good profits, but to do something meaningful to employees, customers, environment and society. As early as 2500years ago, Laozi, an ancient Chinese philosopher, the founder of philosophical Taoism, discovered the role of the Tao or the purpose in life and universe. Wisdom of Taoism has inspired and guided people with precepts of compassion, harmony, cooperation, integrity, humility and prudence. Taoism's thought as the master virtue allows individuals, organizations, and society to cultivate purpose for a sustainable life, and directs leaders to pursue a basic blueprint of not only doing good, but also being good. The purpose of this paper is to blend classical Taoism's wisdom with modern management science to guide leaders to build a responsible and sustainable organization. The paper discussed the relationship between CSR, sustainability and the emerging concept of purpose from philosophical, business and Taoism's perspectives. The author walked readers through the key text of Tao Te Ching to analyze five core principles of Taoism: self-awareness for mindful leadership, self-cultivation for authentic leadership, leading with humility for Level 5 leadership, transcending ego for servant leadership, and doing the right things right for sustainable leadership. The core principles of Taoism shall serve as the foundation for those who want to develop purpose-driven organizations.
Keywords: 650; Purpose; Business; Leadership; Taoism; CSR; Sustainability